Decarboxylative trifluoromethylthiolation of pyridylacetates - Kawanishi, Ryouta; Nakada, Kosuke; Shibatomi, Kazutaka (Beilstein Journal of Organic Chemistry, 2021)
Decarboxylative trifluoromethylthiolation of lithium pyridylacetates was achieved using N-(trifluoromethylthio)benzenesulfonimide as the electrophilic trifluoromethylthiolation reagent. The reaction afforded the corresponding trifluoromethyl thioethers in good yield. Furthermore, the preparation of lithium pyridylacetates by saponification of the corresponding methyl esters and subsequent decarboxylative trifluoromethylthiolation were performed in a one-pot fashion.
Keywords: decarboxylation; fluorinated compounds; pyridine compounds; trifluoromethylthiolation

(untitled) - Taylor, R. D.; MacCoss, M.; Lawson, A. D. G. (J. Med. Chem., 2014)

(untitled) - Vitaku, E.; Smith, D. T.; Njardarson, J. T. (J. Med. Chem., 2014)

(untitled) - Müller, K.; Faeh, C.; Diederich, F. (Science, 2007)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - Zhu, Y.; Han, J.; Wang, J.; Shibata, N.; Sodeoka, M.; Soloshonok, V. A.; Coelho, J. A. S.; Toste, F. D. (Chem. Rev., 2018)

(untitled) - Leo, A.; Hansch, C.; Elkins, D. (Chem. Rev., 1971)

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)

(untitled) - Landelle, G.; Panossian, A.; Leroux, F. R. (Curr. Top. Med. Chem., 2014)

(untitled) - Leroux, F.; Jeschke, P.; Schlosser, M. (Chem. Rev., 2005)

(untitled) - Manteau, B.; Pazenok, S.; Vors, J.-P.; Leroux, F. R. (J. Fluorine Chem., 2010)

(untitled) - Toulgoat, F.; Alazet, S.; Billard, T. (Eur. J. Org. Chem., 2014)

(untitled) - Xu, X.-H.; Matsuzaki, K.; Shibata, N. (Chem. Rev., 2015)

(untitled) - Barata-Vallejo, S.; Bonesi, S.; Postigo, A. (Org. Biomol. Chem., 2016)

(untitled) - Barthelemy, A.-L.; Magnier, E.; Dagousset, G. (Synthesis, 2018)

(untitled) - Shibatomi, K.; Kitahara, K.; Sasaki, N.; Kawasaki, Y.; Fujisawa, I.; Iwasa, S. (Nat. Commun., 2017)

(untitled) - Katada, M.; Kitahara, K.; Iwasa, S.; Shibatomi, K. (Synlett, 2018)

(untitled) - Naruse, A.; Kitahara, K.; Iwasa, S.; Shibatomi, K. (Asian J. Org. Chem., 2019)

(untitled) - Kawanishi, R.; Hattori, S.; Iwasa, S.; Shibatomi, K. (Molecules, 2019)

(untitled) - Kitahara, K.; Mizutani, H.; Iwasa, S.; Shibatomi, K. (Synthesis, 2019)

(untitled) - Kawanishi, R.; Phongphane, L.; Iwasa, S.; Shibatomi, K. (Chem. – Eur. J., 2019)

(untitled) - Shao, X.; Xu, C.; Lu, L.; Shen, Q. (Acc. Chem. Res., 2015)

(untitled) - Liu, X.; An, R.; Zhang, X.; Luo, J.; Zhao, X. (Angew. Chem., Int. Ed., 2016)